2021
DOI: 10.26686/wgtn.14109866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Special issue: Covid-19 and the role of technology and pedagogy on school education during a pandemic

Abstract: No description supplied

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…Various recommendations were made to develop an emergency response plan to prepare the education system for the future (Bokayev et al, 2021;Delcker & Ifenthaler, 2020;Ewing & Cooper, 2021;Palau et al, 2021). The types of preparation that can be done are the development of better infrastructure that allows all students to gain access to high technology; develop and support teacher competence in implementing online pedagogical practices; develop relevant student competencies to carry out individual and collaborative learning using digital technology; and the government provides policies and programs to develop teacher professionalism in the process of changing the education system (Starkey et al, 2021).…”
Section: Education During the Covid-19 Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…Various recommendations were made to develop an emergency response plan to prepare the education system for the future (Bokayev et al, 2021;Delcker & Ifenthaler, 2020;Ewing & Cooper, 2021;Palau et al, 2021). The types of preparation that can be done are the development of better infrastructure that allows all students to gain access to high technology; develop and support teacher competence in implementing online pedagogical practices; develop relevant student competencies to carry out individual and collaborative learning using digital technology; and the government provides policies and programs to develop teacher professionalism in the process of changing the education system (Starkey et al, 2021).…”
Section: Education During the Covid-19 Pandemicmentioning
confidence: 99%
“…The impact of the COVID-19 pandemic on education is an exciting study. Starkey et al (2021) summarize three major themes of issues studied by education experts: technology and digital equality, development of emergency response plans, and appreciation of the role of the teacher. Technological and digital inequalities are impacting the way teachers teach, and students learn at home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies identified its benefits as well as challenges (Adedoyin & Soykan, 2020 [1]; Pham & Ho, 2020 [6]), student satisfaction with online learning (Alkhalilet. al., 2021) [2], the role of technology (Starkey, Shonfeld, Prestridge & Cervera, 2021) [7], e-learning review of literature (Sharin, 2021) [5], etc. Among theories adopted in the past studies are DeLone and McLean's Information Systems Success Model (Lin 2007) [8], Theory of Planned Behaviour (Lim, Seow& Lam, 2020) [9] and the Unified Theory of Acceptance and Use of Technology (UTAUT), combining both student-teacher in a single framework (Umrani-Khan & Iyer, 2009) [10].…”
Section: Problem Statementmentioning
confidence: 99%
“…They can make any communication through digital media which does play significant role, especially at this happening situation (Nurjanah, 2021) . Digital technologies provide teachers and students many features to collaborate, access materials, and have interactive learning (Prastikawati, 2020;Starkey et al, 2021). They may not be afraid of getting bored or not be able to study optimally.…”
Section: Introductionmentioning
confidence: 99%